Implementasi Asas Local Wisdom Dalam Perlindungan dan Pengelolaan Lingkungan Hidup di Desa Wisata Ubud - Putra Prawira Satya Utama; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2025)
Village tourism is important in the world of tourism. But it actually causes exploitation, as for the formulation of the problems taken in this study, namely: (1) How is the implementation of the principle of local wisdom in environmental protection and management in Ubud Tourism Village? (2) How are the supporting and inhibiting factors for the implementation of the principle of local wisdom in the protection and management of the environment in Ubud Tourism Village? The research method used is the type of empirical law research with the type of fact, legislation, and conceptual approach. The results of the study are the implementation of the principle of local wisdom in environmental protection and management in Ubud Tourism Village is carried out traditionally by the Tourism Village Manager, and the surrounding community manages environmental protection with a local wisdom approach. Supporting factors for the implementation of local wisdom principles in environmental protection and management in Ubud Tourism Village are the strong implementation of awig-awig. The inhibiting factor of the implementation of the principle of local wisdom in Ubud Tourism Village is the absence of clear Regional Regulation and lack of socialization.